Examining drama therapy practices through the lens of dis/abled-clinicians-in-training. Issue 2 (1st October 2022) - Cook, Angelle; Young, Kelly; McFann, Caitlin; Angier, Marie
This clinical commentary discusses the experiences of three dis/abled drama-therapy-clinicians-in-training. Through three vignettes, each written by one of the students, reflections and observations are offered on how drama therapy programs may inadvertently support ableist practices and how these can and are being shifted to create more inclusive spaces. Recommendations are offered for drama therapy trainers and students alike, both in the classroom and in the field.